Metastatic Tumours to the Oral Cavity: Report of Three Cases - Ioanna G. Kalaitsidou; Ioannis T. Astreidis; Konstantinos I. Kontos; Maria N. Lazaridou; Eleni T. Bourlidou; Domniki K. Gerasimidou; Natalia P. Vladika; Doxa L. Mangoudi (eJournal of Oral Maxillofacial Research)
Background: Metastatic tumours to the oral cavity from distant organs are uncommon and represent approximately 1 - 3% of all oral malignancies. Such metastases can occur to the bone or to the oral soft tissues. Almost any malignancy from any site is capable of metastasis to the oral cavity and a wide variety of tumours have been reported to spread to the mouth.